Inhibitory Activities of Vegetable Juices on Digestive Enzymes for Starch and Sugar Digestions - Wongon, Matusorn; Muengfa, Kanchana; Trisat, Kanittaporn; Limpeanchob, Nanteetip (Journal of Basic and Applied Pharmacology, 2022)
Hyperglycemia, or raised blood sugar, is a common effect of uncontrolled diabetes. Besides drug therapy, lifestyle modification particularly healthy diet is important. Vegetable-based diet consumption is highly recommended; thus, the present study aimed to investigate and identify type of vegetables possessing potential for management of blood glucose levels. Twenty vegetables were selected to prepare freeze-dried vegetable juices. -Glucosidase inhibitory activity was tested using natural substrates (maltose and sucrose) in comparison with synthetic glucose derivative (pNPG). -Amylase was also tested. The enzyme inhibitory activities of heated-vegetable samples were also monitored to investigate the influence of cooking condition. The result indicated that among all tested samples holy basil, sweet basil, and okra possessed high potential as -glucosidase inhibitors in which 50% inhibitory concentration (IC50) of all three samples were lower than that of acarbose regardless of type of substrates. Juices from holy basil, sweet basil, and okra exhibited non-competitive -glucosidase inhibition whereas acarbose showed competitive inhibition. Boiling differently affected -glucosidase inhibitory activities of each vegetable but it seems not to have much effect on holy basil, sweet basil, and okra activity. In conclusion, consumption of these vegetables may reduce carbohydrate digestion, delay glucose absorption, and reduce postprandial blood glucose that will be benefit not only for diabetic patients but also for people with high risks for developing diabetes, as well as general healthy people.